Assessment and culture : psychological tests with minority populations - Gopaul-McNicol, Sharon-Ann (Practical resources for the mental health professional., 2002)
Assessment and Culture challenges the classical approach to the assessment of minority populations by pointing out the deficiencies in this approach and offers instead a bio-cultural model of assessment. The principle objective of this book is to help mental health professionals to more accurately assess individuals from various ethnic, cultural and linguistic backgrounds. The culture-fair techniques and strategies of the book tap into a broad range of the abilities and aptitudes of the examinee. Assessment and Culture provides a cultural frame of reference which allows the examiner to take into account the individual's social and cultural factors in development, coping style and personal history. Individual chapters consider the practical aspects of assessing the intellectual, linguistic, academic, visual-motor, emotional and vocational functioning of culturally diverse children. An entire section of the book is devoted to writing the assessment report.